Ações educativas sobre prevenção de acidentes infantis em curso de Design Gráfico - Keppler, Maria Aparecida Brandão Bonadio [UNESP] (2013)
Education is indicated as an alternative for the reduction of child accidents, which are a serious worldwide public health problem that is still without a solution. There is a lack of informative material regarded to this theme, available for educational activities with the population, but Graphic Design courses can contribute in their elaboration, however this does not happen. This paper elaborates, applies and evaluates the effect of a teaching program in the knowledge related to the prevention of child accidents and the production of informative materials associated with the theme, with graduate students of Graphic Design course. Forty-nine graduate students of Graphic Design nocturne course took part, at a private Higher Education Institute at a city of the state of São Paulo, Brazil, with nearly 220 thousand inhabitants. It uses printed material, virtual texts and computers equipped with graphic softwares, Moodle environment and internet. As procedure: it elaborates a teaching program based on Behavior Analysis and in the Pilot Study results, with the objective that each participant be able to answer questions, to develop texts and to accomplish the graphic project of informative material related to the theme, as well as to use the project methodology and to produce the final report. It applies the teaching program through the Initial Questionnaire, seeking the identification of the participants’ profile, opinions, previous knowledge and the information they receive at the university about the theme; it accomplishes with the participants activities involving reading, questionnaires, research and elaboration of informative materials associated with the subject and evaluates using the Final Questionnaire to investigate the acquired knowledge and the participants’ opinion related to the accomplished activities; the Activities Registration Spreadsheet elaborated by the researcher to track the participants’ improvement...